The Relationship between Predisposing Factors and Self-care Behaviors among Patients with Rheumatoid Arthritis - M Morowatisharifabad (Ph.D); H Nadrian (MSc.); H Soleimani Salehabadi (MD); SS Mazloomy Mahmoodabad (Ph.D); M Asgarshahi (Ph.D) (Tehran University of Medical Sciences, 2009)
Background & Aim: Self-care activity is a key factor in managing Rheumatoid Arthritis (RA) in order to reduce disability caused by the disease. Predisposing factors including knowledge, attitude, and self-efficacy are introduced as determinants of self-care behaviors in the forth phase of PRECEDE model, i.e., ecological and educational assessment. This study aimed to assess the relationship between the predisposing factors and self-care behaviors in patients with RA in Yazd, Iran. Methods & Materials: In this cross-sectional study, a convenience sampling was used to recruit 181 outpatients with RA referred to a rheumatology clinic in Yazd, Iran. Data were collected by conducting interviews with the participants using a survey questionnaire included knowledge, attitude, and self-efficacy, as predisposing factors; and self-care behaviors items. Reliability and validity of the instruments were examined and approved. The statistical tests included bivariate correlations, Mann-Whitney U test, and linear regression. Results: Knowledge, attitude, and self-efficacy scores were 71.7%, 66.9%, and 47.5%, respectively. The total predisposing factors score was 62.3%. There was a significant positive correlation between the self-care behaviors with attitude and self-efficacy. However, there was no significant correlation between the patients' knowledge and self-care behaviors. Totally, the measures explained 39.3% of total self-care behaviors variance within which the self-efficacy was the strongest predictor (β=0.41). Conclusion: Regarding the high power of predisposing factors, especially self-efficacy, in predicting self-care behaviors; and the low scores of self-efficacy, health promotion planners should pay more attention to predisposing factors of self-care behaviors especially the self-efficacy in designing health promotion programs.   Key words: predisposing factors, rheumatoid arthritis, self-care